Trade policy and industrialization in turbulent times - Helleiner, Gerald K. (Routledge, 1994)
The relationship between trade policy and industrialization has provoked much controversy. Can trade policy promote economic growth in developing countries? Those actively working in the area are becoming increasingly sceptical about the conventional advice given by international policy advisors and organizations. This volume builds upon earlier theoretical and empirical research on trade policy and industrialization but is the first cross-the-board attempt to review developing country experiences in this realm for twenty years. The experience of fourteen developing countries in the 1970s.